2013
DOI: 10.1515/cclm-2012-0593
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath condensate: a comprehensive update

Abstract: Since the late 1990s, a surge in interest in the analysis of exhaled breath condensate (EBC) resulted in the American Thoracic Society and European Respiratory Society (ATS/ERS) organising a Task Force in 2001 to develop guidelines on EBC collection and measurement of biomarkers. This Task Force published their guidelines in 2005 based on literature and expert opinions at that time, and multiple shortcomings and knowledge deficits were also identified. The clinical application of EBC collection and its biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 140 publications
4
77
0
Order By: Relevance
“…This water vapor transports volatile substances coming from the respiratory tract and so pH changes reflecting inflammatory processes can be determined. Although it is recognized that EBC collection and analysis are limited to translational research and not currently used in clinical practice, this being a noninvasive method means it can be repeated in studies monitoring inflammation and longitudinal studies [14]. Recently, the study of EBC has been used to distinguish different phenotypes in asthmatic children [15].…”
Section: Introductionmentioning
confidence: 99%
“…This water vapor transports volatile substances coming from the respiratory tract and so pH changes reflecting inflammatory processes can be determined. Although it is recognized that EBC collection and analysis are limited to translational research and not currently used in clinical practice, this being a noninvasive method means it can be repeated in studies monitoring inflammation and longitudinal studies [14]. Recently, the study of EBC has been used to distinguish different phenotypes in asthmatic children [15].…”
Section: Introductionmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A c c e p t e d M a n u s c r i p t It has been suggested that lyophilisation may be useful for reducing variability by concentrating samples thereby raising biomarkers away from the lower end of assay sensitivity. There are a lack of studies examining the reliability and reproducibility of this method (51). Unfortunately the only studies in this review to have used this approach (Battaglia et al (20) and Sood et al (19)) concentrated their samples to differing levels (threefold and fourteenfold respectively).…”
Section: Discussionmentioning
confidence: 99%
“…EBC is representative of the airway lining fluid (ALF) of the respiratory tract [3]; therefore, its analysis of EBC could lead to identify potential biomarkers with capability to reflect the underlying state of pulmonary inflammation and alteration in various respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), bronchiectasis, infections, cystic fibrosis, primary ciliary dyskinesia or even lung cancer [4][5][6]. In this context, EBC could be an alternative sample to those obtained by cumbersome and invasive techniques such as bronchoscopy with bronchoalveolar lavage or sputum induction.…”
Section: Introductionmentioning
confidence: 99%